Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1128/jcm.35.12.3171-3180.1997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of use of phenotypic and genotypic characteristics for identification of species of the anamorph genus Candida and related teleomorph yeast species

Abstract: A total of 49 type and neotype isolates and 32 clinical isolates of the anamorph genus Candida and related teleomorph genera were obtained from different culture collections and clinical laboratories. Isolates were subjected to two phenotypic methods of identification, Vitek yeast biochemical card (YBC) and API ID 32C, both based on carbohydrate assimilation, and one genotypic method, PCR fingerprinting, based on the detection of DNA polymorphisms between minisatellite-specific sequences with the primer M13 (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 28 publications
0
17
0
3
Order By: Relevance
“…Many variables including culture medium and the incubation temperature influenced the characteristics of both strains. 12,13 Conventional phenotypic methods although convenient to perform, was unable to identify the isolate. In this case study, the Vitek 2 system indicated the yeast isolate as C. famata.…”
Section: Discussionmentioning
confidence: 99%
“…Many variables including culture medium and the incubation temperature influenced the characteristics of both strains. 12,13 Conventional phenotypic methods although convenient to perform, was unable to identify the isolate. In this case study, the Vitek 2 system indicated the yeast isolate as C. famata.…”
Section: Discussionmentioning
confidence: 99%
“…In this study fourteen research brewing yeast strains, three wild type S. cerevisiae isolates, one Polish production strain and three type strains were examined. 16,19,20) were isolated from two Polish breweries 4 and identified using…”
Section: Yeast Strainsmentioning
confidence: 99%
“…18) and the three isolates from the brewing industry (No. 16,19,20) gave identical patterns in each RFLP analyses and were grouped in OP IV. The OP IV group was different from the others using the HaeIII restriction profile.…”
Section: Numerical Analysismentioning
confidence: 99%
See 2 more Smart Citations